Influence of alcohol consumption on blood coagulation in ROTEM: an in-vivo study - Eismann, Hendrik; Sieg, Lion; Ahmed, Hala; Teske, Joerg; Behrendt, Patrick; Friedrich, Lars; Schumacher, Carsten; Johanning, Kai (Korean journal of anesthesiology, 2020)
Background: Twenty-five to 85% of trauma patients are under the influence of alcohol in addition to experiencing injury-related coagulation impairment. Viscoelastic point-of-care tests (thrombelastography [TEG], rotational thromboelastometry [ROTEM]) are popular tools for rapid hemostasis assessment and therapeutic decision-making in this and other settings. While alcohol affects these tests in-vitro, their specific effects in-vivo are unclear. Therefore, we evaluated the effects of alcohol ingestion on ROTEM parameters.Methods: Twenty volunteers provided informed consent to drinking red wine, whisk(e)y, or vodka to a target blood alcohol concentration of 1 ‰ within one hour, calculated with the Widmark formula. Blood samples were collected before drinking, at a breath alcohol concentration of 0.5 ‰, and at 1.0 ‰, but no later than one hour. After each blood collection, ExTEM and FibTEM tests were performed directly "at the bedside."Results: All participants had a blood alcohol concentration (BAC) of 0.00 ‰ at the beginning. The mean BACs at the second and third collection were 0.48 and 0.76 ‰, respectively. There were no significant differences in the ExTEM parameters. FibTEM measurements showed a significant difference at the A10 value (13.0 vs. 14.0 mm, P = 0.014) and a trend at the maximum amplitude (maximum clot firmness [MCF] 13.7 vs. 16.2 mm, P = 0.075). We saw no significant differences in fibrinolysis parameters and no hyperfibrinolysis in our ROTEM measurements.Conclusions: Ethanol ingestion can impair early fibrin polymerization. These results might be of special relevance in trauma and support routine application of ROTEM/TEG in such cases.